If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6+2(3x-2)=-4(2+x)
We move all terms to the left:
6+2(3x-2)-(-4(2+x))=0
We add all the numbers together, and all the variables
2(3x-2)-(-4(x+2))+6=0
We multiply parentheses
6x-(-4(x+2))-4+6=0
We calculate terms in parentheses: -(-4(x+2)), so:We add all the numbers together, and all the variables
-4(x+2)
We multiply parentheses
-4x-8
Back to the equation:
-(-4x-8)
6x-(-4x-8)+2=0
We get rid of parentheses
6x+4x+8+2=0
We add all the numbers together, and all the variables
10x+10=0
We move all terms containing x to the left, all other terms to the right
10x=-10
x=-10/10
x=-1
| -6(3k-1)=114 | | 6x-68=x | | 3(a+1.5=-1.5 | | 9+6x=12+5x | | 17+4m=25 | | X-9=2x-22 | | 5=3v+6+8 | | 13+6/5x=23-9x | | 7+2k=-3 | | 15=4(g−16)−-15 | | 6+2{3x-2}=-4{2+x} | | -1-6(k-5)=65 | | 1-9x=136 | | 2/5m−1/5=540 | | x/17=45 | | 2/5=3x+9/4x-2 | | X+2=4+2x-8 | | 1=1-7v-2v | | 4x-3(x+4)=9(x-2) | | c/4+15=16 | | 25m−15=540 | | -78=-6f+6 | | 23-9x=13+6/5x | | 2(6x-15)=2x-5 | | 31+7q=94 | | 14x+9=7x+1 | | -a+8-3a=16 | | v/7-61=-56 | | z/8-33=36 | | -9+2=-2n-8 | | X-2x=4+2x-8 | | X-1/x-2+x-2/x-1=5/2 |